The hallmarked man [large type] - Galbraith, Robert (Galbraith, Robert. Cormoran Strike novel, 2025)
"A dismembered corpse is discovered in the vault of a silver shop. The police initially believe it to be that of a convicted armed robber -- but not everyone agrees with that theory. One of them is Decima Mullins, who calls on the help of private detective Cormoran Strike as she's certain the body in the silver vault was that of her boyfriend -- the father of her newnorn baby -- who suddenly and mysteriously disappeared. The more Strike and his business partner Robin Ellacott delve into the case, the more labyrinthine it gets. The silver shop is no ordinary one: it's located beside Freemasons' Hall and specializes in Masonic silverware. And in addition to the armed robber and Decima's boyfriend, it becomes clear that there are other missing men who could fit the profile of the body in the vault."--Provided by publisher.